Capitalization of land development rights in rural China: A choice experiment on individuals' preferences in peri-urban Shanghai. (September 2020) - Wen, Lanjiao; Chatalova, Lioudmila; Butsic, Van; Hu, Fox ZhiYong; Zhang, Anlu
Highlights: The value of land development rights is sensitive to land attributes and individuals' characteristics. Individuals' expectations of capitalizing land development rights vary with development type. The possibility to state individual preferences improves the compensation standard. Abstract: The capitalization of land development rights is acknowledged as the key to improving compensations for rural landholders and ameliorating land-related social conflicts in peri-urban China. Investigations into reasonable as well as feasible compensation standards and the capitalization mechanism are yet to be done. This study uses a survey-based choice experiment to empirically estimate the value of land development rights in peri-urban Shanghai for three forms of rural land conversion – acquisition, consolidation and (informal) sale. The results show that heterogeneity across individuals' preferences translates into different utilities from land development, which affects individual's willingness to participate in this process. This effect is found to be the strongest for land sales on the informal market. If, however, land conversion is managed by local governments and rural collectives, the expected utilities of individuals have no significant effect on the amount of land development. The results suggest that capitalizing land development rights under consideration of land attributes and individuals' preferences would lift compensation standard to a level that strikes a balance among competing land-related interests. In addition, it would promote China's land development by bypassing the institutional constraints imposed by the current land tenure system.